2021
DOI: 10.2147/dddt.s308610
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study to Evaluate the Safety, Tolerability, and Pharmacokinetics of TPN171H, a Novel Phosphodiesterase Type 5 Inhibitor, in Healthy Subjects

Abstract: Purpose: TPN171H is a novel, potent and selective phosphodiesterase type 5 (PDE5) inhibitor for the treatment of pulmonary arterial hypertension (PAH). The objective of this study was to evaluate the safety, tolerability, and pharmacokinetics of TPN171H in healthy subjects after single and multiple dosing, in addition, to investigate the food effect on pharmacokinetics and safety of TPN171H. Methods: The entire study was comprised of three parts: Part I (single ascending-dose study), Part II (food effect study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In vitro experiments revealed that its PDE5 inhibitory activity was stronger than sildenafil and tadalafil. Phase-1b clinical trials have been completed with good safety and tolerability [ 113 , 114 , 115 ], and a phase-2a multicenter, randomized, placebo- and positive-controlled study (NCT04483115) is ongoing to assess its acute hemodynamic effects in PAH patients.…”
Section: Potential Drugs Being Investigatedmentioning
confidence: 99%
“…In vitro experiments revealed that its PDE5 inhibitory activity was stronger than sildenafil and tadalafil. Phase-1b clinical trials have been completed with good safety and tolerability [ 113 , 114 , 115 ], and a phase-2a multicenter, randomized, placebo- and positive-controlled study (NCT04483115) is ongoing to assess its acute hemodynamic effects in PAH patients.…”
Section: Potential Drugs Being Investigatedmentioning
confidence: 99%